Large-scale serial replacement of invasive tench (Tinca tinca) by invasive carp (Cyprinus carpio) in the presence of redfin perch (Perca fluviatilis) in the Murray-Darling River system, Australia - Matthew P. Hill; Peter Caley; Ivor Stuart; Richard P. Duncan; David M. Forsyth (Biological Invasions, 2024)
Ecosystems worldwide are increasingly being invaded by multiple species, and the rate of biological invasion is accelerating, leading to more interactions among invasive species. One such interaction that has received little attention is the phenomenon of ‘serial replacement’ or ‘over-invasion’, where an established invasive species is supplanted by a second invasive species. Understanding this interaction is important as controlling the second species could inadvertently lead to an increase in the abundance of the first species. We used a hierarchical state-space model to analyse changes in annual abundances (commercial catch-per-unit-effort) of three invasive fish species, tench ( Tinca tinca ), common carp ( Cyprinus carpio ) and redfin perch ( Perca fluviatilis ), in the Murray-Darling River system (MDRS), Australia between 1954–2002. Tench were present at low abundances until the mid-1970 s, before declining to the point of no commercial catch post-1989. This rapid decline coincided with a significant increase in carp abundance, suggesting that carp may have driven the tench decline through habitat modification (particularly the destruction of aquatic plants), consistent with findings from European studies that show the disappearance of tench from ponds with intensive carp farming. Redfin perch populations, were inferred to be much less impacted by the invading carp population. While carp were present in the MDRS for the duration of the study, the rapid increase in carp abundance in the early 1970 s coincided with the introduction of a specific genetic lineage—the “Boolarra strain”. Our analysis provides compelling evidence of serial replacement of long-established tench by invading common carp triggered by the introduction of a novel carp strain.

Complexity-functioning relationships differ across different environmental conditions - Mariana Mayer-Pinto; Amelia Caley; Antony M. Knights; Laura Airoldi; Melanie J. Bishop; Paul Brooks; Ricardo Coutinho; Tasman Crowe; Paolo Mancuso; Lais P.D. Naval-Xavier; Louise B. Firth; Rafael Menezes; et al. (Journal of Environmental Management, 2024)

On inferring population trends of mobile waterbirds from aerial transect surveys in variable environments - Peter Caley; Julian R. W. Reid; Matthew J. Colloff; Simon C. Barry (Environmental and Ecological Statistics, 2022)
Monitoring waterbird populations in Australia is challenging for reasons of counting logistics, and because population aggregation and dispersion can shift rapidly in response to large spatio-temporal variations in resource availability. The East Australian Waterbird survey has conducted annual, aerial, systematic counts of waterbirds over eastern Australia for almost 40 years. It was designed to monitor waterbird populations using design-based inference though for many species this form of inference appears inadequate in the face of these challenges. Here we develop a state-space model-based Bayesian approach that, in addition to explicitly incorporating process noise and observation uncertainty, uses random effects and rainfall-derived covariates to model the year-to-year variation in the proportion of the total (super) population that is present on surveyed wetlands, and available to be counted. We use this model-based approach to estimate the superpopulation size of 45 waterbird species annually, and model the rate of population increase as a function of antecedent rainfall. The results confirm the strong positive effect of antecedent rainfall on population growth rates for nearly all species, and illustrate that species respond to rainfall differently in terms of habitat use, which influences whether they are present on surveyed wetlands. For many species, the year-to-year variation in the estimated proportion of the population on surveyed wetlands is very high. The results have implications for making inferences on population trends from these data, with the ability to model the year-to-year sampling variation a key requirement before the rate of population increase can be estimated with any precision. This study illustrates how to progress this approach, and infers that under average rainfall conditions, the general trend is for estimated superpopulation rates of increase to be negative, though for only a few species is this occurring with strong belief.

When exotic introductions fail: updating invasion beliefs - Daniel K. Heersink; Peter Caley; Dean Paini; Simon C. Barry (Biological Invasions, 2020)
Decisions regarding invasive risk of exotic species are often based on species distribution models projected onto the recipient region of interest. Such projections are essentially a measure of prior belief in the ability of an organism to invade. Whilst many decisions are made on the basis of such projections, it is less clear how such prior belief may be empirically modified on the basis of data, in particular introduction events that haven’t led to establishment. Here, using the Asian green mussel ( Perna viridis ) as an example, we illustrate how information on failed introduction attempts may be used to continually update our beliefs in the ability of an organism to invade per introduction, and the underlying habitat suitability for establishment. Our results show that the establishment probability of P. viridis per fouled ship visit in the supposedly favourable northern Australian waters are much lower than initially though, and are continuing to decline. A Bayesian interpretation of our results notes the dramatic reduction in our belief of the ability of P. viridis to invade in the light of what we estimate to be 100’s of fouled vessels per year visiting ports without any persistent populations establishing. Under a hypothetico-deductive approach we would reject the null (prior) species distribution model as being useful, and seek to find a better one that can withstand the challenge of data.

Crowd surveillance: estimating citizen science reporting probabilities for insects of biosecurity concern - Peter Caley; Marijke Welvaert; Simon C. Barry (Journal of Pest Science, 2020)

Statistical modeling of a larval mosquito population distribution and abundance in residential Brisbane - Daniel K. Heersink; Jacqui Meyers; Peter Caley; Guy Barnett; Brendan Trewin; Tim Hurst; Cassie Jansen (Journal of Pest Science, 2016)

Entry of exotic insects into Australia: Does border interception count match incursion risk? - Peter Caley; Robert Ingram; Paul De Barro (Biological Invasions, 2015)

An aboveground–belowground assessment of ecosystem properties associated with exotic annual brome invasion - Caley K. Gasch; Stephen F. Enloe; Peter D. Stahl; Stephen E. Williams (Biology and Fertility of Soils, 2013)

Accounting for detection probability when estimating force-of-infection from animal encounter data - Paul B. Conn; Evan G. Cooch; Peter Caley (Journal of Ornithology, 2012)

Quantifying uncertainty in predictions of invasiveness, with emphasis on weed risk assessment - Peter Caley; W. M. Lonsdale; P. C. Pheloung (Biological Invasions, 2007)

Quantifying uncertainty in predictions of invasiveness, with emphasis on weed risk assessment - Peter Caley; W. M. Lonsdale; P. C. Pheloung (Biological Invasions, 2006)

Quantifying Uncertainty in Predictions of Invasiveness - Peter Caley; W. M. Lonsdale; P. C. Pheloung (Biological Invasions, 2006)